2019
DOI: 10.1002/mds.27911
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Toll‐Like Receptor 4 (TLR4) and Triggering Receptor Expressed on Myeloid Cells 2 (TREM2) Genetic Variants and Clinical Progression of Huntington's Disease

Abstract: Background Although Huntington's disease (HD) is caused by a single dominant gene, it is clear that there are genetic modifiers that may influence the age of onset and disease progression. Objectives We sought to investigate whether new inflammation‐related genetic variants may contribute to the onset and progression of HD. Methods We first used postmortem brain material from patients at different stages of HD to look at the protein expression of toll‐like receptor 4 (TLR4) and triggering receptor expressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Notably, in these same brain regions in PD, we also observed increased expression of IL-1β, a downstream product of the inflammasome pathway which is triggered by TLR4 activation. Interestingly, TLR2 and TLR4 have also been implicated in other proteinopathies, including Alzheimer's [69] and Huntington's disease [73] raising the possibility of a common pathogenic mechanism across several neurodegenerative diseases. The concomitant increase in the gene expression of TLR4 and IL-1β in the substantia nigra and the frontal cortex suggests an involvement of the NODlike receptor protein 3 (NLRP3) inflammasome in these regions, with TLR4 activation resulting in increased expression of pro-IL-1β as well as NLRP3 activation; in turn, NLRP3 inflammasome activation could be responsible for the cleavage of pro-IL1β to the mature protein.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in these same brain regions in PD, we also observed increased expression of IL-1β, a downstream product of the inflammasome pathway which is triggered by TLR4 activation. Interestingly, TLR2 and TLR4 have also been implicated in other proteinopathies, including Alzheimer's [69] and Huntington's disease [73] raising the possibility of a common pathogenic mechanism across several neurodegenerative diseases. The concomitant increase in the gene expression of TLR4 and IL-1β in the substantia nigra and the frontal cortex suggests an involvement of the NODlike receptor protein 3 (NLRP3) inflammasome in these regions, with TLR4 activation resulting in increased expression of pro-IL-1β as well as NLRP3 activation; in turn, NLRP3 inflammasome activation could be responsible for the cleavage of pro-IL1β to the mature protein.…”
Section: Discussionmentioning
confidence: 99%
“…Another report of Alzheimer's disease is that the significantly decreased plaque load observed in APP transgenic and APOE or TREM2 knockout mice (Krasemann et al, 2017). At the same time, TREM2 is a potential genetic modifier of Huntington's disease (HD), and its expression is related to the TLR4 receptor (Vuono et al, 2020). In vascular dementia (VD), TREM2 regulates the microglial activation phenotype to improve disease progression (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to what has been reported for Trem1, activation of Trem2 results in a diminished endogenous inflammatory response 54 . In studies carried out in monocytes and microglial cells, Trem2 was found to interact with bacterial cell surface carbohydrates 55,56 and to down‐modulate TLR‐mediated cellular activation 29–31 . While both Trem1 and TremL2 have been detected on neutrophils, 57 no previous reports document the expression and/or function of Trem or Trem‐like proteins in human or mouse eosinophils.…”
Section: Resultsmentioning
confidence: 89%
“…Trem2 has been characterized primarily on monocytes, dendritic cells, and microglia. Trem2 promotes cell proliferation and differentiation 26–28 and limits inflammation via modulation of TLR responses 29–31 …”
Section: Introductionmentioning
confidence: 99%